Impact of left atrial appendage closure on left atrial hemodynamics: a prospective single center study. (25th November 2020) - Mertens, E; Bouziri, N; Guedeney, P; Duthoit, G; Redheuil, A; Ceccaldi, A; Chicheportiche, T; Isnard, R; Silvain, J; Montalescot, G; Hammoudi, N
Abstract: Background: Percutaneous left atrial (LA) appendage closure is increasingly used to prevent strokes in patients with atrial fibrillation (AF). While LA appendage plays a key role in LA physiology, data regarding the impact of LA appendage occlusion on LA hemodynamics are lacking. The alteration of LA compliance by LA appendage occlusion may represent a clinical issue in AF patients which are at high risk of heart failure. Purpose: To describe the impact of LA appendage occlusion on LA hemodynamics. Material and methods: From july 2015 to january 2020, all patients undergoing LA occlusion procedure at Pitié-Salpêtrière Hospital (Paris, France) in whom LA pressure curves were recorded, before and immediately after device implantation, were included. The LA mean pressure was measured at baseline and after LA appendage occlusion during the same procedure. Abnormal LA mean pressure was defined as >15mmHg. We also recorded cardiovascular death and hospitalization for congestive heart failure at longest follow-up. Results: We enrolled 85 patients (78±8 years, 46 men), the CHA2DS2-VASc score was 5±1 and the HAS-BLED score was 4±1. The mean LA volume index was 51±15mL/m 2, the left ventricular ejection fraction was 60±7%. The LA mean pressure increased significatively after LA appendage closure from 12.6±3.9mmHg to 15.5±5.2mmHg (p<0.0001, Figure). The prevalence of abnormal LA pressure was 20% (17/85) at baseline and 45% (38/85) after LA appendage closure (p=0.005). Post procedural LA pressure elevation was not related to procedure duration nor to fluid expansion volume. During a median follow-up of 364 [124–726] days, 3 (3.5%) patients died from a cardiovascular cause. Hospitalization for heart failure occurred in 6 (16%) of the 38 patients with abnormal postprocedural LA pressure, whereas no congestive episode was observed in the rest of the study population (p=0.006). Conclusion: Catheter-based LA appendage occlusion induces an acute alteration of LA hemodynamics. Post procedural abnormal LA pressure may be linked to heart failure episodes in some patients. Further studies are warranted to investigate heart failure as a potential late complication of LA appendage closure. Funding Acknowledgement: Type of funding source: None